2010
DOI: 10.1123/japa.18.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Can Aerobic Training Improve Muscle Strength and Power in Older Men?

Abstract: This study examined the effect of aerobic training on leg strength, power, and muscle mass in previously sedentary, healthy older men (70–80 yr). Training consisted of 30–45 min of cycle ergometry at 50–70% maximal oxygen consumption (VO2max), 3 times weekly for 16 wk, then 4 wk detraining, or assignment to a nontraining control group (n= 12 both groups). Training increased leg strength, leg power, upper leg muscle mass, and VO2maxabove pretraining values (21%, 12%, 4%, and 15%, respectively;p< .05). Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 38 publications
7
39
0
5
Order By: Relevance
“…Possibly a higher training frequency (>3 days per week) may be required to achieve a large number of muscle contractions that places a high-volume, low-load on skeletal muscle compared to RE training (Harber et al, 2009; Konopka et al, 2010). However, others have found that AE significantly increased muscle strength outcomes with a training frequency similar to ours (3 times a week) (Lovell, Cuneo, & Gass, 2010; Misic, Valentine, Rosengren, Woods, & Evans, 2009). Our findings may be related to some distinct mechanisms involved in aerobic activities performed overground, treadmill or cycle ergometers (Prosser, Stanley, Norman, Park, & Damiano, 2011).…”
Section: Discussionsupporting
confidence: 69%
“…Possibly a higher training frequency (>3 days per week) may be required to achieve a large number of muscle contractions that places a high-volume, low-load on skeletal muscle compared to RE training (Harber et al, 2009; Konopka et al, 2010). However, others have found that AE significantly increased muscle strength outcomes with a training frequency similar to ours (3 times a week) (Lovell, Cuneo, & Gass, 2010; Misic, Valentine, Rosengren, Woods, & Evans, 2009). Our findings may be related to some distinct mechanisms involved in aerobic activities performed overground, treadmill or cycle ergometers (Prosser, Stanley, Norman, Park, & Damiano, 2011).…”
Section: Discussionsupporting
confidence: 69%
“…The role of the other correspondingly different variables is less clear. The hypertrophic effects of aerobic training have been equivocal and somewhat controversial (Harber et al, 2012;Lundberg et al, 2013), but several studies have shown increased muscle mass and increased slow oxidative fibre size after aerobic exercise training in mammals, including humans (Schwartz et al, 1991;Schluter and Fitts, 1994;Trappe et al, 2006;Harber and Trappe, 2008;Harber et al, 2009Harber et al, , 2012Konopka et al, 2010;Lovell et al, 2010). However, although FCSA certainly contributes to force production, it is less clear how a larger FCSA might increase endurance.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, to facilitate the development of a training habit, it is better that exercisers do not feel fatigue. Muscle strength significantly decreases when training is stopped; if training is resumed, its muscle strengthening effects are then less than they were previously24 ) . Therefore, training should consist of exercises that are easy to continue.…”
Section: Discussionmentioning
confidence: 97%
“…The few studies that have shown positive effects of exercise on the mass and strength of the thigh muscles used brisk walking, jogging at 85% HR reserve21 ) , or interval training at 70% to 85% VO 2 peak6, 22 ) as exercises. Cycling at 70% VO 2 max or 80% HR reserve has been shown to increase quadriceps muscle strength and power and thigh muscle volume23, 24 ) . Aerobic exercise can increase muscle strength and mass depending on the intensity, frequency, and duration of the exercise.…”
Section: Discussionmentioning
confidence: 99%